(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2026)
This text presents the 32nd edition of Móin-Móin - Journal of Animated Form Studies, themed “The stage of celebration: Puppet Theater, ritual, festivity, and community”. It details its composition context, the questions that challenged the authors, and an invitation to read the published articles.